The Difference of EPDS Examination Results before and after Delivery in High-Risk Pregnant Woman at Unair Hospital - Delvanny Alfikri Rekaputri Wicaksono; Agustina Konginan; Nalini Muhdi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Pregnancy is an exceptional condition for a woman who will become a mother. Theprospective mother will experience a phase to continue the offspring, and depression is a complicationthat generally does not occur in childbirth. Objective: To determine the differencein the prevalence ofdepression through the results of the EPDS examination before and after delivery in high-risk pregnantwomen at Unair Hospital. Method: This research will use an observational analytic study design witha one-group pretest-posttest design strategy—data retrieval using primary and secondary data, namelyby questionnaires and medical records at Unair Hospital. The sample in this study consisted of 23multigravida pregnant women and one primigravida mother who sought treatment at the OutpatientInstallation of Unair Hospital in March 2021 - May 2021. Results: The prevalence of pregnant womenwith a tendency to postpartum depression on the EPDS scores before and after delivery are 8% and17%, respectively. There is a very weak positive correlation between pre-delivery EPDS scores andpost-delivery EPDS scores. Conclusion: There is no significant difference between the scores beforeand after delivery in a high-risk pregnant woman at Unair Hospital.